The Development of the Iqrak Model Based on Al-Ghazali’s Philosophy in Teaching and Learning Among SRAJAIM Teachers in the 21st Century - Mohamad Rohana, Noor Aziera; Surtahman, Asma’ Wardah; P. Rameli, Mohd Faizal; Abdul Razak, Abdul Qayuum; Halim, Faiqah Hafidzah; Johari, Muhd Khudri (Millah: Journal of Religious Studies, 2026)
Education is a key factor in strengthening the direction of a civilisation, and in Malaysia, its implementation is based on the National Education Philosophy (NEP). The 21st-century education emphasizes knowledge delivery, innovation, technological competence and the holistic and integrated development of human capital. Teaching and learning (T&L) conducted by teachers at Religious Primary Schools (SRA) under the supervision of the Melaka Islamic Religious Department (JAIM) follows the curriculum of the Department of Islamic Development Malaysia (JAKIM). However, research on the development of contemporary pedagogical methods remains limited. This study identifies the key elements contributing to the effectiveness of teaching and learning among SRAJAIM teachers based on Al-Ghazali’s educational principles, which emphasize the balance between character, knowledge and practice, and develops a context-appropriate T&L model. The qualitative study employed literature review and focus group discussions (FGD) involving approximately 40 informants, with data analysed using NVivo software. The findings indicate that the T&L practices of SRAJAIM teachers are consistent with the NEP, particularly with regard to lifelong learning and holistic integrated approaches. Accordingly, the IQRAK Model was developed as a novel contribution and represents the first structured T&L model specifically designed and implemented within the JAIM education system to strengthen human capital development in a holistic and balanced manner.